2013
DOI: 10.1021/mp300613x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Monitoring of Pulmonary Fibrosis by Targeting Matrix Metalloproteinases (MMPs)

Abstract: While idiopathic pulmonary fibrosis (PF) is a devastating lung disease, the management of PF including effective monitoring of disease progression remains a challenge. Herein, we introduce a novel, fast and ultra-sensitive metalloproteinase (MMP) activatable optical probe, named MMP-P12, to non-invasively monitor PF progression and response to PF treatment. A bleomycin (BLM)-induced mouse PF model was subjected non-invasively to optical imaging at various time points after BLM treatment. Mouse PF model develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…[49] Similarly, increased expression of α v -integrin, a potential activator of MMPs, [50] correlates with increased lung fibrosis in young mice, [36] as seen in the current aged male BLM model. Importantly, we found that expression of α v -integrin mRNA is lower in donor yASCs compared to donor oASCs at baseline.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[49] Similarly, increased expression of α v -integrin, a potential activator of MMPs, [50] correlates with increased lung fibrosis in young mice, [36] as seen in the current aged male BLM model. Importantly, we found that expression of α v -integrin mRNA is lower in donor yASCs compared to donor oASCs at baseline.…”
Section: Discussionmentioning
confidence: 95%
“…[38] Increased activity of MMPs is directly associated with ECM turnover in IPF [13, 44, 45] and in other fibrotic diseases. [4648] Higher MMP-2/9 activity and expression has been demonstrated in young [49] and aged mice [13] following BLM infusion. Although we focused on MMP-2, it should be pointed out that current studies suggest that multiple MMPs (1, 2, 7, 9, and 13) are important to the pathogenesis of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05 day post-BLM administration. In BLM-induced lung fibrosis, a coincidental increase of gelatinase activity and disruption of the alveolar epithelial basement membrane have been found [25]. It was indicated that MMP2 may play a role in a later phase in regard to the formation of the fibrotic foci, thereby facilitating subepithelial myofibroblast migration to the alveolar lumen [1,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive labeling allows for regional dosimetry via X-ray tomography (CT), PET and SPECT, but not for determination of the bioactivity of the substances. On the other hand, fluorescent substances including nanoparticles have been widely used for preclinical dosimetry studies both in vitro and in vivo [7,8] and numerous fluorescent probes are available for studying the bioactivity of drugs in terms of activation/deactivation of complex biological processes in living animals. Consequently, using innovative preclinical strategies of optical imaging has allowed in vivo real-time insight not only in genomics and proteomics ([9] and references 1-6 herein), but also in disease state of animal models such as the size of cancer lesions or of a remodeled bone [10].…”
Section: Introductionmentioning
confidence: 99%